Produksi Pakan Berbahan Baku Utama Maggot pada Kegiatan Budi Daya Ikan Lele di Belinyu, Kabupaten Bangka - Eva Prasetiyono Pras; Eva Utami; Teguh Iskandar; Endah Prihatini Isnawati (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
One of the main problems in aquaculture is cost of fish feed. Self made feed can reduce cost for buying commercial feed. Maggot is an organism that can be used as an ingredient in making independent feed. The purpose of this activity is to disseminate technology by utilizing maggot as the main raw material in making own fish feed to minimize production costs.This activity was carried out in fish farmers. They are located in Dusun Bukit Dempo, Kelurahan Bukit Ketok, Kecamatan Belinyu, Kabupaten Bangka. The method was carried out by disseminating technology in making fish feed based on maggot raw materials using simple applied technology. The use of fish feed from maggot raw materials was be able to catfish harvests and reduced the use of commercial fish feed, thereby minimizing production costs. The results of the economic calculation of the comparison of the use of commercial feed with feed from maggot flour in catfish cultivation resulted in a margin of Rp. 399,000 for a stocking density of 1,000 fish with a survival rate of 80% and a harvest size of 7 fish/kg. Feed from maggot flour can be consumed by cultivated Catfish and increase the weight and normal growth of Catfish.